Pelatihan Pembuatan Laporan Keuangan Bagi UMKM Sebagai Informasi Untuk Pengambilan Keputusan - Wisnantiasri, Sila Ninin; Sofia, Irma Paramita; Nurhidayah, Fitriyah; Sunaryo, Karsam (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2018)
The purpose of this dedication for Pisangan Village Community through financial statement training for small business in collaboration with partners of Citra Kencana Community is to improve the understanding of partners in making financial report especially income statement. The problem facing partners is not mastering how to create a correct financial statement. The financial statements can be used by partners as a benchmark of business performance and business financial analysis tools. Therefore, the methods used in this activity are: (1) convey material about basic concepts of accounting, (2) convey material about components of income statement, (3) provide business simulation and recording financial statements through educational game business accounting (4) the practice of preparing the business income statement and analysis by the entrepreneur, (5) advising / consulting the profit-loss statement. Besides, regression test is done through event study approach to know the impact of training for knowledge of financial report objectives and understanding of financial reporting from the community after getting the training. The result of this activity is increasing both knowledge and understanding of society in making financial report. This is shown by the direction of a positive and significant relationship between training with community knowledge and understanding. Keywords: Financial statement, Small entrepreneurship, Business analysis